2014
DOI: 10.1088/1054-660x/24/2/025601
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of glucose levels in mouse blood with noninvasive optical methods

Abstract: We report the quantification/monitoring of glucose levels in a blood sample using optical diffuse reflectance (ODR) underlying variations in optical parameters with a white light source (at peak wavelength ∼600 nm and range 450-850 nm) and in blood in vivo using M-mode optical coherence tomography (OCT) in terms of the translational diffusion coefficient (D T ). In the ODR experiments, we have investigated two types of mono-dispersive particles, i.e. polystyrene microspheres (PMSs) with diameters of 1.4 µm (va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Agar and blood ROIs were chosen as indicated in (a). ACF analysis (Figure 6 (b)) shows that while agar pixels decorrelate within ~160 ms, stationary and flowing blood decorrelate much faster (~20 and 4 ms, respectively), which is in agreement with previously reported measurements [39]. With increasing time, ACFs tend to approach zero as in the previous experiment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Agar and blood ROIs were chosen as indicated in (a). ACF analysis (Figure 6 (b)) shows that while agar pixels decorrelate within ~160 ms, stationary and flowing blood decorrelate much faster (~20 and 4 ms, respectively), which is in agreement with previously reported measurements [39]. With increasing time, ACFs tend to approach zero as in the previous experiment.…”
Section: Resultssupporting
confidence: 91%
“…ACF analysis ( Figure 5 (b)) shows that microtube wall pixels (green curve) decorrelate much slower than stationary (blue curve) and flowing (red curve) suspension with decorrelation times of the latter yielding 3.3 and 1.5 ms at 1/e level, respectively. The faster decorrelation in the presence of flow makes sense and has been previously reported by several groups [37][38][39]. We thus note that flow conditions do make a difference, and all ACF curves tend to zero with increasing time as expected.…”
Section: Resultssupporting
confidence: 85%
“…This method presents some advantages over others due to its capability to measure concentration in situ without interrupting the process as well as the simple post processing work thereafter. As such, the method has been used since in the early 1990s up until recently (Maier et al 1994, Chance et al 1995, Liu et al 1996, Tuchin et al 1997, Wang 2000, Vargas et al 2001, Yao et al 2002, Bashkatov et al 2003, Zhang et al 2013a,b, Trichet et al 2014, Ullah et al 2014, Pleitez et al 2015.…”
Section: Refractive Index Methodsmentioning
confidence: 99%
“…There seems to be no recent study reported on the use of refractive index method to monitor the glucose diffusion in TE materials. However, this method has been used recently to measure glucose level in tissue sample, and one such study is reported by Ullah et al (2014), where they used the refractive index method to measure the glucose level in mouse blood. The aim of their study was to further understand the use of laser applications to determine blood glucose levels without incision.…”
Section: Refractive Index Methodsmentioning
confidence: 99%
“…It is based on Michelson The delay correlation between the reflected light in the reference arm and backscattered light in the sample arm is measured [11]. The idea of the mismatching refractive index between reference and sample indices has a potential application to measure the glucose level in blood both in vivo and vitro, using optical coherence tomography [100]. The (OCT) technology allows to measure the glucose induced changes in skin directly from the dermis layer [101].…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%